DeLone and McLean Sebagai Model Pengukuran Layanan Informasi Tanggap Covid-19 - Wisnu Nicola; Tri Lathif Mardi Suryanto; Asif Faroqi (STMIK Banjarbaru, 2022)
The Surabaya City Government is trying to improve the efficiency and effectiveness of the performance of handling the Covid-19 virus through the “Fight Covid-19 Web” concept. However, the use of the website as a medium for information on the spread of the Covid-19 virus still has limitations, so it is deemed necessary to conduct a study (measurement) of the web-based Covid-19 response information service. This study aims to measure the success factors of the Web Against Covid-19 and examine the relationship between variables on net benefits. The research uses the Updated 2003 Information System Success Model, with six measurement variables, namely information quality, system quality, service quality, use, user satisfaction, and net benefit. As many as 400 residents of the city of Surabaya and its surroundings who have accessed the website against Covid-19 were selected as respondents. The results showed that information quality and system quality variables had a positive and significant effect on net benefits through the use of variable mediation, while service quality variables had a negative and insignificant effect on net benefits through use variable mediation. The results also show that the use variable has a positive and significant effect on net benefits through the mediation of the user satisfaction variable.Keywords: Information system success model; Net benefit; DeLone and McLeanAbstrak. Pemerintah Kota Surabaya berupaya meningkatkan efisiensi dan efektivitas penanganan virus Covid-19 melalui konsep Web Lawan Covid-19. Namun pemanfaaan website sebagai media informasi persebaran virus Covid-19 masih memiliki keterbatasan, sehingga dipandang perlu melakukan kajian (pengukuran) terhadap layanan informasi tanggap Covid-19 berbasis web tersebut. Penelitian ini bertujuan menganalisis faktor-faktor keberhasilan Web Lawan Covid-19 dan menguji hubungan antar variabel terhadap net benefit. Penelitian menggunakan model Information System Success Model Updated 2003, dengan enam variabel pengukuran yaitu information quality, system quality, service quality, use, user satisfaction, dan net benefit. Sebanyak 400 penduduk kota Surabaya dan sekitarnya yang telah mengakses web Lawan Covid-19 dipilih sebagai responden. Hasil penelitian menunjukan Variabel information quality dan system quality memiliki pengaruh positif dan signifikan terhadap net benefit melalui mediasi variabel use, sedangkan variabel service quality berpengaruh negatif dan tidak signifikan terhadap net benefit melalui mediasi variabel use. Hasil penelitian juga menunjukkan variabel use memiliki pengaruh positif dan signifikan terhadap net benefit melalui mediasi variabel user satisfaction.Kata kunci: Information system success model; Net benefit; DeLone dan McLean